THE USE OF PARALLEL CORPORA IN DEVELOPING TRANSLATION COMPETENCE (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
The use of parallel corpora has become a pivotal methodological resource in developing translation competence, offering translators systematic access to authentic bilingual texts that reveal patterns of lexical choice, syntactic alignment, and pragmatic equivalence across languages. By enabling learners to observe real-world translation solutions, parallel corpora create an evidence-based learning environment where decisions are grounded in empirical language behavior rather than intuition alone. This approach fosters deeper awareness of translational norms, variation, and genre-specific conventions, while simultaneously enhancing critical analytical skills such as contrastive reasoning, error detection, and strategic problem-solving. As a result, parallel corpora serve not only as reference tools but also as dynamic pedagogical instruments that support the acquisition of professional competence, empowering translators to make informed, context-sensitive choices and to refine their stylistic precision in both source and target languages.